2004
DOI: 10.1111/j.1478-3231.2004.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen induces suppression of cell viability and apoptosis in the human hepatoblastoma cell line HepG2 via down‐regulation of telomerase activity

Abstract: The tamoxifen-induced reduction of cell viability in HepG2 cells depends on drug concentration and cell density and is due to cytostatic and cytocide effects. The latter may be mediated by a down-regulation of telomerase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
(51 reference statements)
2
22
0
Order By: Relevance
“…has been described for a number of chemotherapeutic drugs such as tamoxifen [40], doxorubicin and vincristine [41]. Kobayashi et al [41] demonstrated that at high cell densities, a decreased cellular uptake of chemotherapeutics results in attenuated availability 19 of drug molecules at its intracellular binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…has been described for a number of chemotherapeutic drugs such as tamoxifen [40], doxorubicin and vincristine [41]. Kobayashi et al [41] demonstrated that at high cell densities, a decreased cellular uptake of chemotherapeutics results in attenuated availability 19 of drug molecules at its intracellular binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while the rate of apoptotic nuclei was still low (about 5%) following 24 hour incubation of the cells, it increased up to 63% when the incubation time was prolonged to 72 hours (33). In another study which was carried out by the same researchers, it has shown that tamoxifen does not affect the transcription level olf hRT, hTERT, and TP1 in HepG2 cells.…”
Section: Discussionmentioning
confidence: 90%
“…The mechanisms of tamoxifen action in HCC, however, are not yet clearly understood. Results from studies on the human hepatoblastoma cell line HepG2 provide evidence that estrogen-receptor-a-independent antiproliferative actions of tamoxifen in HCC are mediated by the suppression of telomerase activity [5]. Materials and methods: We investigate the pathway of the tamoxifen-induced down-regulation of telomerase activity, using HepG2 cells incubated over 24 h or 48 h in the presence of 20 lM tamoxifen.…”
mentioning
confidence: 99%